Orbital Floor Fractures in Germany: Interdisciplinary Care without a Uniform Standard – Results of a Multicentre Survey - Holtmann, Christoph; Roth, Mathias; Szurman, Gesine; Grenzebach, Ulrike; Schrage, Norbert; Brinkmann, Christian; Wabbels, Bettina; Dick, Burkhard; Kohlhaas, Markus; Freißler, Gernot; Schargus, Marc; Hesse, Lutz; Roider, Johann; Wykrota, Agata Anna; Müller, Arthur; Sauder, Gangolf; Tost, Frank; Walther, Jürgen; Scheider, Andreas; Maier, Mathias M.; Hartmann, Kathi; Bertelmann, Eckart; Hintschich, Christoph; Ladewig, Markus; Eckstein, Anja; Reinhard, Thomas; Schittkowski, Michael P.; Rokohl, Alexander C.; Heindl, Ludwig Maximilian; Sterker, Ina; Grisanti, Salvatore; Renieri, Giulia; Elflein, Heike Maria; Brockmann, Tobias; Krauss, Patrizia; Hufendiek, Karsten; Besgen, Volker; Ruediger, Katja; Heichel, Jens; Viestenz, Arne; Borrelli, Maria; Geerling, Gerd (Klinische Monatsblätter für Augenheilkunde, 2025)
Objective Surgical treatment of orbital floor fractures (OFF) in Germany is performed by several subspecialties. In an emergency setting, the question of necessity and urgency of surgery is frequently answered without ophthalmological consultation.Purpose The aim of this survey was to investigate the current management of OFF in German centres with emergency care, among the members of the national oculoplastic society (Section Ophthalmoplastic and Reconstructive Surgery [SORC]).Methods An 11-question questionnaire was sent to the main ophthalmology departments and members of the Section for Ophthalmic Reconstructive Surgery (SORC). Open (2), semi-open/multiple choice variant with multiple choice (6) and closed/dichotomous questions were used (3).Results The questionnaire response rate was 36.3% (37/102). Patients with OFF are treated by oral and maxillofacial surgeons at 86.1% of the sites and by ear, nose and throat specialists (in some cases interdisciplinary) at 25% of the sites. When the indication for surgery was made, the orthoptic status was only carried out at 72% of the sites and preoperative imaging was carried out at 75%. At 58.3% of the sites, OFF correction was also performed without any preoperative clarification by an ophthalmologist, predominantly in cases of polytrauma. The time of surgery was between 0 and 25 days, with a median of 7 days after the accident (8 ± 6 days).Conclusions In Germany, the initial surgical treatment of OFF is predominantly performed without prior ophthalmologic consultation and not by ophthalmologists. As early reconstruction can cause considerable individual ophthalmologic loss of function, it is important to promote interdisciplinary cooperation and, in particular, the corresponding oculoplastic care expertise in ophthalmology in order more reliably to avoid inadequate indications. The development of an interdisciplinary S2 guideline and the establishment of a national registry for orbital floor fractures appear to be urgently required to improve the quality of care.Hintergrund Die chirurgische Versorgung von Frakturen des Orbitabodens (OBF) wird in Deutschland von mehreren Fachdisziplinen vorgenommen. Die Frage der Notwendigkeit und der Dringlichkeit einer Operation wird gerade in der Notfallversorgung auch ohne ophthalmologische Konsultation beantwortet.Fragestellung Ziel dieser Umfrage war es, in Zentren mit augenärztlicher Notfallversorgung und unter den Mitgliedern der DOG-Sektion „Ophthalmoplastische und rekonstruktive Chirurgie“ (SORC) einen Überblick über die Versorgungssituation dieser Patienten in Deutschland zu gewinnen.Methoden Ein 11 Aspekte umfassender standardisierter Fragebogen wurde an die Hauptabteilungen für Augenheilkunde und Mitglieder der Sektion ophthalmoplastisch-rekonstruktive Chirurgie (SORC) versandt. Es wurden offene (2), halboffene/Multiple-Choice-Variante mit Mehrfachauswahl (6) und geschlossene/dichotome Fragen verwendet (3).Ergebnisse Die Fragebogen-Rücklaufquote betrug 36,3% (37/102). Patienten mit OBF werden an 86,1% der Standorte von Mund-Kiefer-Gesichtschirurgen und an 25% der Standorte durch (z. T. interdisziplinär) Hals-Nasen-Ohrenärzte behandelt. Bei der medizinischen Indikationsstellung zur Operation wurde nur bei 72% der Standorte der orthoptische Status und bei 75% eine präoperative Bildgebung durchgeführt. An 58,3% der Standorte erfolgte eine OBF-Korrektur sogar ohne jegliche präoperative Diagnostik durch einen Augenarzt, überwiegend bei Polytraumata. Der Zeitpunkt der Operation lag zwischen 0 und 25 Tagen im Median 7 Tage nach dem Unfall (8 ± 6 Tage).Fazit Die operative Erstversorgung von OBF wird in Deutschland häufig ohne vorherige augenärztliche Konsultation und nicht von Augenärzten durchgeführt. Eine OBF stellt jedoch in aller Regel keine medizinische Indikation zur Notfalloperation dar. Da eine frühzeitige Rekonstruktion in erheblichem Maße individuelle ophthalmologische Funktionseinbußen auslösen kann, gilt es neben der interdisziplinären Zusammenarbeit insbesondere die entsprechende okuloplastische Versorgungskompetenz in der Augenheilkunde zu fördern, um inadäquate Indikationsstellung sicherer zu vermeiden. Die Entwicklung einer interdisziplinären S2-Leitlinie sowie die Etablierung eines nationalen Registers für Orbitabodenfrakturen erscheinen für die Verbesserung der Versorgungsqualität dringend erforderlich.
Keywords: orbit; fracture; surgery; survey; treatment